Microencapsulação de conídios de Trichoderma asperellum por spray drying para produção de fungicida microbiológico - Braga, Alinne Brandão Andalécio Camargos (2018)
The excessive use of agrochemicals in agriculture to control plant diseases has given rise to several environmental problems. In this way, alternative methods that aim at environmental sustainability have been proposed, among which biological control has been highlighted. Fungi of the genus Trichoderma spp. have the most used species for phytopathogen control in the world, but the formulated products present reduced shelf life and biological agent viability during storage and field application. In addition, the integration of chemical and biological treatments into seeds can lead to damage to microorganisms. Therefore, it has been sought to promote a protection of these agents to increase their viability, through the use of microencapsulation techniques. The objective of this work was to characterize different types of wall materials, sucrose, maltodextrin DE20, Arabic gum, whey and lactose, and to apply them in the microencapsulation process by means of preliminary tests in order to identify an encapsulating agent with potential; By means of a central composite planning (PCC) to optimize and validate the statistical model obtained to represent the microencapsulation process of the conidia of Trichoderma asperellum by spray drying using maltodextrin DE20 as encapsulating agent; Characterization of the microparticles produced by tests of moisture, water activity, water solubility, hygroscopicity, viable conidia (CV), percentage of conidial survival (SP), optical microscopy, scanning electron microscopy (SEM) and particle size distribution; To evaluate the shelf life of microencapsulated conidia by spray drying and to apply them to chemically treated soybean seeds by chemical and untreated fungicides and insecticides in order to ascertain conidia resistance to chemicals and storage over time. In the evaluation of the results, it was noticed that the addition of the wall materials allowed an increase in the germination and viability of the conidia of Trichoderma asperellum in comparison with the tests without the use of protective wall material, being that the best results of CV (%) and SP (%) were found using maltodextrin DE20, followed by whey. To study the stability of dehydrated microparticles through moisture sorption isotherms. The values optimized by PCC were 80°C for the drying air intake temperature and 1:4.5 dry mass of Trichoderma asperellum conidia/dry mass of maltodextrin DE20. Under the optimized conditions it was obtained experimentally drying yield of 63.85 ± 0.86%, moisture of 4.92 ± 0.07%, viable conidia of 87.10 ± 1.16% and survival percentage of 85.78 ± 2.88%. The conidia showed high viability after 150 days of storage at 4 °C, exhibiting approximately 2,17×109 CFUg-1 . Microencapsulation proved to be efficient for the integration of biological treatment with chemical products in soybean seeds. The results obtained with this study are promising, demonstrating that the conidia of Trichoderma asperellum microencapsulated can be an alternative to reach longer shelf life and chemical compatibility during the storage of seeds, aiming to obtain methodologies for sustainable agriculture. Experimental values of the isotherms microencapsulated conidia demonstrated that the adsorptive properties of the powder were significantly affected by the presence of maltodextrin DE20 in the product formulation, since the control sample obtained lower moisture adsorption indices. The moisture sorption isotherms of the conidia of Trichoderma asperellum microencapsulated by spray drying were well adjusted by the BET model (R2 of 0.989) and characterized as type III, while the control and PCT samples were better adjusted by the model of GAB (R2 of 0.927 and 0.947).